(untitled) (Vietnam Journal of Community Medicine, 2022)
The study was conducted on 123 patients who had to undergo placenta previa caesarean section at Thai Binh Obstetrics and Gynecology Hospital from June 1, 2019 to the end of May 31, 2020. The results showed that: The rate of emergency surgery accounted for 40.7%, the cause of bleeding accounted for 82%. The transverse incision in the lower uterine segment is the main one, accounting for 91.1%. Management of hemostasis during colorectal surgery: medical success was 44.7%, hemostasis in the area of ​​fascia was 29.3%, Aortic utery ligation (alone and in combination) was successful 20.3%. Active hysterectomy is operated in placenta increta or failed hemostasis. The rate of organ damage is 1.65%, mainly in placenta increta. The rate of preterm cesarean section of placenta previa is 30.9%, the neonatal mortality rate is 1.6%. The rate of blood transfusion after surgery of placenta previa is 21.1%, mainly in emergency surgery and central placenta previa.